USING PICTURES SERIES IN INCREASING STUDENT’S WRITING SKILL TO THE ELEVENTH GRADE STUDENTS OF SMA PGRI 2 PALEMBANG - Etty Pratiwi (Global Expert: Jurnal Bahasa dan Sastra, 2017)
This research investigated  of using pictures series in increasing student’s writing skill  to the eleventh grade students of SMA PGRI 2 Palembang. The objective of this study was to identify whether or not by using pictures series can increase the students ‘ writing skill. This study was conducted in experimental research to 165 students from the eleventh grade students of SMA PGRI 2 Palembang of the academic years of 2016-2017. This study could be concluded that pictures series strategy gave a significant increase for the students’ writing skill than the students’ writing skill by using conventional strategy to the eleventh grade students of SMA PGRI 2 Palembang. Key words: Pictures stories, Writing skill, Experimental research